The Human Rights Conditions That Affect Politics and Government Stability in The United Kingdom - R. Cornell, Rachel (Jurnal Daulat Hukum, 2024)
In 2023, the UK government eroded domestic human rights protections and reneged on important international obligations. The government passed a law further criminalizing protesters and limiting workers’ strikes. A new law will ban people who arrive “irregularly” to the UK from claiming asylum or accessing protection, putting them at further risk of harm. This paper will discuss about government who again failed to take meaningful steps to tackle institutional racism and address past wrongs, including to fairly compensate Black Britons whose rights were harmed by government policies in what was coined the “Windrush scandal” and to remedy ongoing colonial crimes against the Chagossian people. The UK’s nose-diving domestic human rights record undermined its efforts to promote the rule of law and human rights globally.